In‐Plane Uniaxial Strain in Black Phosphorus Enables the Identification of Crystalline Orientation. Issue 30 (9th June 2017) - Zhang, Shuqing; Mao, Nannan; Wu, Juanxia; Tong, Lianming; Zhang, Jin; Liu, Zhirong
Abstract : Identification of the crystalline axis of anisotropic black phosphorus (BP) is important for investigating its physical properties, as well as for optical and electronic applications. Herein, it is showed that by applying in‐plane uniaxial strain and measuring the changes of the Raman shifts, the crystalline axis of BP can be reliably determined. The strain effects on the Raman shifts are angle‐dependent, and they can be expressed as a combination of the Raman responses under zigzag and armchair strain. Differing from previous polarized optical spectroscopic methods where the Raman intensity is analyzed, the proposed method uses the Raman frequency shift, which is less affected by laser polarization, excitation wavelength, the sample thickness, and the substrate. The effective strain applied on BP from the stretched substrate is estimated, and the results show that only 20 to 40% of the strain can be effectively transferred to BP flakes from a polyethylene terephthalate substrate. Our method provides not only an effective and robust approach to identify the crystalline orientation of layered BP, but it is also a model to extract additional information in strain‐related studies. It can also be extended to other 2D anisotropic materials. Abstract : To identify the crystalline orientation of anisotropic layered black phosphorus (BP), an effective and robust approach is developed by strain effects on the Raman shifts. The method shows that only 20–40% of the strain can be directly and effectively transferred to BP flakes from a polyethylene terephthalate substrate, which is instructive for investigating other 2D materials.